2011
DOI: 10.1590/s0100-69912011000400002
|View full text |Cite
|
Sign up to set email alerts
|

Estudo descritivo dos casos de câncer de mama em Goiânia, entre 1989 e 2003

Abstract: The topographical location and histological type of breast cancer in the city of Goiania followed the pattern of other countries. The main morphological types were not influenced by age. There was a large increase in initial cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 16 publications
1
8
0
1
Order By: Relevance
“…In this retrospective analysis, the results are comparable with data from international literature and population-based studies in Brazil regarding the median age at diagnosis and menopause as the most frequent status in women with breast cancer, [26][27][28][29][30] biologic prognostic tumor like HR status, HER2 and histological subtypes. [31][32][33] The current study demonstrated that patients in local advanced stages, III and IV, were 19% and 8% respectively, which was comparable to data from Brazilian studies.…”
Section: Discussionsupporting
confidence: 82%
“…In this retrospective analysis, the results are comparable with data from international literature and population-based studies in Brazil regarding the median age at diagnosis and menopause as the most frequent status in women with breast cancer, [26][27][28][29][30] biologic prognostic tumor like HR status, HER2 and histological subtypes. [31][32][33] The current study demonstrated that patients in local advanced stages, III and IV, were 19% and 8% respectively, which was comparable to data from Brazilian studies.…”
Section: Discussionsupporting
confidence: 82%
“…22 In this study, the highest occurrence of metastasis (25.2%) in a five-year period was verified between 2008 and 2013 in Goiania-GO, compared with 10.20% for distance metastasis in the same city in the period from 1989 to 2003. 26 This increase may be explained by technological advancements that facilitated the identification of breast cancer recurrence over the years. 27 …”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, opportunistic breast cancer screening in some areas of Brazil and the use of mammography (12,13) have allowed the reduction of local advanced diseased and an increase in early breast cancer detection (14). However, as of 2004, this modification in the pattern of diagnosis had not affected breast cancer mortality (15,16), morbidity, or quality of life, considering different types of surgical treatment (17).…”
Section: Introductionmentioning
confidence: 99%